Personality Classification on Twitter Social Media using BERT - Yantrisnandra Akbar Maulino; Warih Maharani; Prati Hutari Gani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
In the modern era, social media is a platform often used to interact with people. Twitter is a popular social media, especially for human interaction. Using tweets on Twitter can describe how a person's personality and can also describe characteristics of a person. Humans themselves based on the Big Five Model Nursing Theory (Big Five Personality), have five general personalities, namely openness, conscientiousness, extraversion, agreeableness, and neuroticism. Personality itself influences a person's judgment of many things, knowing the personality of a person can make it easier to know the characteristics, habits, and ways of that person in their daily activities. In addition, understanding someone's personality can be a reference in seeing how someone can interact with others. It can also be used when looking for a job according to their personality. Thus, this research builds a system to classify personality using the BERT model with the dataset used in the form of tweets from Twitter users by making several changes such as parameters and using tests with several ratios in determining test data and also training data. The results acquired in this study are 50%.